+0  
 
0
54
2
avatar

If (cos(A) - sin(A))/(cos(A) + sin(A)) = (1 - sqrt(3))/(1 + sqrt(3)) and 0 < A < 90, then find A.

 Dec 22, 2019
 #1
avatar
0

zvvvv

 Dec 22, 2019
 #2
avatar+106519 
+1

cos A - sin A                      1 - sqrt (3)                

____________ =              ____________                       cross -  multiply    

cos A + sin A                      1 +  sqrt (3)

 

 

(cos A - sin A) ( 1 + sqrt (3))  =  (cos A + sinA) ( 1 - sqrt (3) )

 

cosA + sqrt (3)cos A  - sin A - sqrt (3)sin A    =   cos A - sqrt(3)cos A  + sin A  - sqrt (3) sin A

 

Simplify as

 

2sqrt(3) cos A  = 2sin A  

 

sqrt (3) cos A = sin A

 

sqrt (3) = sin A  / cos A

 

sqrt (3)  = tan A

 

arctan ( sqrt (3) ) =  A  =    60°

 

 

 

cool cool cool

 Dec 22, 2019

6 Online Users

avatar